Use of Hydrophilic Insoluble Polymers in the Restoration of Metal-Contaminated Soils - Guiwei Qu; Amarilis de Varennes (Applied and Environmental Soil Science)
To develop cost-effective techniques that contribute to phytostabilization of severely metal-contaminated soils is a necessary task in environmental research. Hydrophilic insoluble polymers have been used for some time in diapers and other hygienic products and to increase the water-holding capacity of coarse-textured soils. These polymers contain groups, such as carboxyl groups, that are capable of forming bonds with metallic cations, thereby decreasing their bioavailability in soils. The use of polyacrylate polymers as soil amendments to restore metal-contaminated soils has been investigated in the Technical University of Lisbon since the late nineties. Plant growth and plant nutrients concentrations, extractable levels of metals in soil, and soil enzyme activities were used to monitor the improvement in soil quality following the application of these polymers. In contaminated soils, hydrophilic insoluble polymers can create microcosms that are rich in water and nutrients (counterions) but only contain small concentrations of toxic elements; the conditions of these microenvironments are favorable to roots and microorganisms. In this paper we described the most relevant information available about this topic.